2020
DOI: 10.1186/s12986-019-0421-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of beetroot (Beta vulgaris) in management of cardio-metabolic diseases

Abstract: Red beetroot (Beta vulgaris), as a naturally occurring root vegetable and a rich source of phytochemicals and bioactive compounds, is known for its beneficial roles in the improvement of several clinical and pathologic outcome. Chronic and acute beetroot juice supplementation, as a cost-effective strategy, is proposed to hold promises in controlling diabetes and insulin hemostasis, blood pressure and vascular function, renal health and the possible effect on microbiome abundance. The secondary outcome and phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
78
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 74 publications
(92 reference statements)
3
78
0
9
Order By: Relevance
“…In addition, it contains many functional constituents such as polyphenols, vitamins, minerals, and others. Therefore, BV is considered as a medicinal plant with hepatoprotective and antioxidant effects and can be used in the treatment of several diseases [11]. In the present study, the functional constituents and antioxidant properties of BVJ were examined to explain its expected hepatoprotective action against Pb intoxication in rats.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it contains many functional constituents such as polyphenols, vitamins, minerals, and others. Therefore, BV is considered as a medicinal plant with hepatoprotective and antioxidant effects and can be used in the treatment of several diseases [11]. In the present study, the functional constituents and antioxidant properties of BVJ were examined to explain its expected hepatoprotective action against Pb intoxication in rats.…”
Section: Introductionmentioning
confidence: 99%
“…An epidemiological study involving 1938 healthy adults showed that intake of adequate phytochemicals was beneficial, lowering body weight and body fat. [10] Sulforaphane (SFN), an isothiocyanate found in cruciferous vegetables, especially in broccoli, was reported to regulate a number of metabolic enzymes including phase I & phase II metabolic enzymes, and lipid metabolism-related enzymes/proteins. [11] Oral administration of the sulfur-radish extract and sulforaphane after carbon tetrachloride (CCl 4 )-induced liver injury decreased the serum level of alanine aminotransferase (ALT), reduced the necrotic zones, inhibited lipid peroxidation, and induced phase 2 enzymes without affecting cytochrome P450-2E1 (CYP2E1).…”
Section: Introductionmentioning
confidence: 99%
“…SFN decreased the lipid accumulation in vivo and in vitro. Three doses of SFN(5,10, and 20 mg kg -1 ) and PPC (30 mg kg -1 ) were orally gavaged to rats three times a week along with HFD diet. And HHL-5 hepatocytes were pretreated with SFN (1, 5, 10, 20 μmol L -1 ) for 24 h, followed by 0.25 mmol L -1 FAs (oleic acid: palmitic acid, 2:1) for 5 days.…”
mentioning
confidence: 99%
“…It therefore lacks a large amount of recent studies performed in this rapidly growing field of research. Reviews analyzing the effect of BRJ on broader subject populations were not systematic reviews and again mostly only included a specific outcome, such as the effect on training physiology and performance (Olsson et al 2019), or the properties of BRJ in relation to cardiometabolic disorders (Mirmiran et al 2020). Other reviews again focus on the effect of BRJ on specific populations, such as the effect on women , or the effect on exercise performance in heart failure with reduced ejection fraction (Mulkareddy et al 2019).…”
Section: Introductionmentioning
confidence: 99%